Freedom's Witness : The Civil War Correspondence of Henry McNeal Turner - Turner, Henry McNeal, 1834-1915 (Book collections on Project MUSE., 2013)
In a series of columns published in the African American newspaper The Christian Recorder, the young, charismatic preacher Henry McNeal Turner described his experience of the Civil War, first from the perspective of a civilian observer in Washington, D.C., and, later, as one of the Union army's first Black chaplains. In the halls of Congress, Turner witnessed the debates surrounding emancipation and Black enlistment. As army chaplain, Turner dodged "grape" and cannon, comforted the sick and wounded, and settled disputes between white southerners and their former slaves. He was dismayed by the destruction left by Sherman's army in the Carolinas, but buoyed by the bravery displayed by Black soldiers in battle. After the war ended, he helped establish churches and schools for the freedmen, who previously had been prohibited from attending either. Throughout his columns, Turner evinces his firm belief in the absolute equality of Black people with their white peers, and insists on civil rights for all Black citizens. In vivid, detailed prose, laced with a combination of trenchant commentary and self-deprecating humor, Turner established himself as more than an observer: he became a distinctive and authoritative voice for the Black community.